Adaptação e propriedades psicométricas da Eskin’s Attitudes Towards Suicide Scale (E-ATSS) e Eskin’s Social Reactions to Suicidal Persons Scale (E-SRSPS) para o português brasileiro - Nespollo, Alice Milani (2021)
ABSTRACT: Adapting the “Eskin's Attitudes Towards Suicide Scale” (E-ATSS) and the “Eskin's Social Reactions to Suicide Persons Scale” (E-SRPSS) to Brazilian Portuguese and evaluate the psychometric properties in a sample of university professors. Method: A methodological study which adapted the E-ATSS and E-SRPSS, based on the steps of translation, synthesis of translations, back-translation, expert committee, pre-test and feedback to the author. The experts committee was composed of 10 experts and the pre-test was carried out with 31 professors from the Federal University of Mato Grosso (UFMT). To obtain evidences of internal structure, the instruments were applied to a sample of 367 UFMT professors. The survey was carried out between July, 2018 and December, 2019. The analyzes were performed by calculating the Content Validity Index (CVI), Confirmatory Factor Analysis (CFA), Exploratory Factor Analysis (EFA), analyzes based on the Item Response Theory (IRT) by the Rating Scale model, and the reliability was tested by Cronbach's alpha, McDonald's omega and Intraclass Correlation Coefficient (ICC). Results: In the evaluation process by the experts committee, two items from the E-ATSS and three from the E-SRPSS had a CVI lower than recommended and were changed. At the end of the adaptation, the scales were named Eskin’s Scale of Attitudes to Suicide and Eskin’s Scale of Social Reactions to Suicidal People. Regarding to EFA, the final model for the Eskin’s Attitudes Towards Suicide Scale resulted in four factors and 16 items with CFI indexes = 0.996; TLI = 0.993; RMSEA (95% CI) = 0.030 (0.0067-0.0578) and explained variance of 79.85%. For the Eskin’s Scale of Social Reactions to Suicidal Persons, the adjustment indices showed adequate from the one-dimensional model with seven items (CFI = 0.984; TLI = 0.977; RMSEA (95% CI) = 0.071 (0.0333-0.0915) and explained variance of 58.66%. In the analyzes based on the IRT, in the Eskin’s Scale of Attitudes Related to Suicide, most of the items showed difficult to be endorsed, while in the Eskin’s Scale of Social Reactions to Suicide Persons the items were easily endorsed by the sample. For the response categories of Likert scale, the five points were discriminative on both scales. The reliability of the Eskin’s Attitudes Towards Suicide Scale was obtained by Cronbach's alpha values of 0.931, 0.951, 0.974 and 0.848, McDonald's omega of 0.935, 0.954, 0.975 and 0.857, and CCI 0.914, 0.948, 0.737, 0.816 for Factors 1, 2, 3 and 4 respectively. The Eskin’s Scale of Social Reactions to Suicidal Persons was obtained by Cronbach's alpha of 0.863, McDonald’s omega of 0.881 and CCI for items which ranged between 0.409 and 0.737. Conclusion: according to the analyzes which were carried out, the Eskin’s Scale of Attitudes Related to Suicide was adequate for using for Brazilian university professors and, although the validation process of Eskin’s Scale of Social Reactions to Suicide Persons had resulted in the exclusion of items, the instrument also proved to be valid for using for Brazilian university professors.